Sex differences in knee joint laxity change across the female menstrual cycle - Shultz, S. J.; Sander, T. C.; Kirk, S. E.; Perrin, D. H. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: To elucidate the hormonal influences on sex differences in knee joint behavior, normal-menstruating females were compared to males on serum hormone levels and anterior knee joint laxity (displacement at 46N, 89N and 133N) and stiffness (Linear slope of DForce/DDisplacement for 46-89N and 89-133N) across the female menstrual cycle. Methods: Twenty-two females were tested daily across one complete menstrual cycle, and 20 males were tested once per week for 4 weeks. Five days each representing the hormonal milieu for menses, the initial estrogen rise near ovulation, and the early and late luteal phases (total of 20 days) were compared to the average value obtained from males across their 4 test days. Results: Sex differences in knee laxity were menstrual cycle dependent, coinciding with significant elevations in estradiol levels. Females had greater laxity than males on day 5 of menses, days 3-5 near ovulation, days 1-4 of the early luteal phase and days 1, 2, 4 and 5 of the late luteal phases. Within females, knee laxity was greater on day 5 near ovulation compared to day 3 of menses, and days 1-3 of the early luteal phase compared to all days of menses and day 1 near ovulation. On average, differences observed between sexes were greater than those within females across their cycle. There were no differences in anterior knee stiffness between sexes or within females across days of the menstrual cycle. Conclusion: These results suggest sex hormones may be a primary mediator of the observed sex differences in knee laxity.